Tension-Based Reconfigurable Multi-Agent Formation for Aerial Load Transportation - Vinicius Pacheco Bacheti; Daniel K. D. Villa; Rogelio Lozano; Mario Sarcinelli-Filho; Pedro Castillo (IEEE Access, 2025)
This paper proposes a trajectory tracking controller for a cable-suspended load transported by n uncrewed aerial vehicles (UAVs) based on Euler angle states. This is accomplished using the resultant tension on the load as a virtual input and then distributing it to each vehicle, for which low-level controllers generate the correct thrust and torque values. Furthermore, a leader-follower-based control is proposed to safely change the number of agents carrying the load. Numerical simulations are presented to validate the controllers. Finally, experiments demonstrate that the proposed method effectively enables the load to perform as expected and allows for the configuration of the formation to be changed without significantly impacting the load navigation.